Development of STEM Integrated Flipped Classroom Learning Program to Improve Students' Systems Thinking Skills - Fatoni Latif; Abdurrahman; Noor Fadiawati (Jurnal Penelitian Pendidikan IPA, 2024)
This research develops a Flipped Classroom integrated with STEM with the ADDIE model to improve systems thinking skills. The research subjects were 31 students at Al Kautsar Middle School in Bandar Lampung. At the beginning of the research, it was found that 70% of teachers had not used the flipped classroom, 65% had not integrated STEM, 73% had not understood systems thinking skills which was carried out on 30 teachers, and performance analysis was carried out on 60 students, with the results of 72% learning traditionally, 73% had not integrated STEM and the average value of systems thinking skills is 40. Validators stated that the development instrument was valid with values of 92.12 and 92.52% when limited testing was carried out. Assessment of learning implementation was 89% and assessment of student performance was 88%. The program is effective in improving systems thinking skills in terms of an N-Gain of 0.58 and an effect size of 0.22 in the medium category. Effectiveness is supported by practicality 88%, positive teacher response 88%, and positive student response 81% with very high criteria. The research results concluded that the STEM-integrated flipped classroom program was effective and practical in improving systems thinking skills.